Fabrication and characterization of ZnO nanostructures for DNA detection - Foo, Kai L0ong
Zinc oxide (ZnO), a representative of group II-IV metal-oxide semiconductor material is widely studied in the current research community. ZnO with its wide direct band-gap (3.37eV) and high exciton binding energy (60meV) providing the advantages of their electrical and optical properties. Due to these unique properties and easiness to grow using bottom-up approach combines with high isoelectric point, toxic-free, high surface-area-to-volume ratio, biosafe, and biocompatible, ZnO nanostructures have great interest in the application of biosensor. The aim of this research work is to synthesis, fabricate, and characterize ZnO nanostructures based sensor for DNA immobilization and hybridization detection. Two types of ZnO nanostructures were studied, namely thin films and nanorods (NRs). Highly transparent ZnO thin films were successfully synthesized using ease and low-cost sol-gel spin-coating method. ZnO NRs with nanoscale possessed high crystalline structure was further grown from the asprepared thin films through low-temperature hydrothermal growth. In this thesis, we studied the influence of different solvents on the structure, optical and electrical properties of the ZnO nanostructures. Four types of solvents namely methanol, ethanol, isopropanol, and 2-methoxyethanol had been chosen for ZnO seed solution preparation. The observed results using FESEM indicated that the nanoparticles and nanorods with the size less than 40 nanometer and 60 nanometer, respectively were successfully synthesized. The investigation on optical properties using UV-Vis-NIR spectrophotometer confirmed ZnO is classified as a wide band gap semiconductor material. In order to fabricate a biosensor with high sensitivity and selectivity, a gold nanoparticles (GNPs) were selected for the surface modification of ZnO nanostructures which later formed gold-thiolate conjugation with thiol-modified ssDNA probes. Two approaches were used for the immobilization and hybridization of DNA detection, which were dielectric analysis and electrochemical analysis. DNA detection using dielectric analyzer was done on interdigitated electrodes gold modified ZnO thin films. The developed sensor clearly differentiated complementary and non-complementary of target DNA through the measurement of capacitance, permittivity, and impedance. DNA detection using electrochemical analysis with cyclic voltammetry confirmed surface ZnO NRs modified with (3-Aminopropyl)triethoxysilane (APTES) and gold nanoparticles provided better detection of target DNA in comparison with those only contained gold nanoparticles.